# Math

posted by .

expand and simplify

1. -(y^2-4y+7)(3y^2-5y-3)

2.2(a+b^3

• Math -

1. -(y^2 - 4y + 7)(3y^2 -5y -3) =
-3y^4 + 5y^3 + 3y^2 + 12y^3 - 20Y^2- 12y -21Y^2 + 35Y + 21 =
-3Y^4 + 17Y^3 - 38Y^2 + 23Y + 21 =

2. 2(a + b^3) = 2a + 2b^3. This one was already simplified.

## Similar Questions

1. ### math

how do i expand and simplify (2x+5) (3x-4)
2. ### math

expand and simplify (2x+5)(3x-4)
3. ### math

expand and simplify 4(3k-2)+3(4-k)
4. ### Math

Expand and simplify 1.(9a-3)^2 2.(x^2+2x-1)^2 3. 2(3a+4)(a-6)-(3-a)^2+4(5-a)
5. ### math

expand and simplify 1.(x^2-3x+4)(-x^2+3x-4) 2.3(2x-5)-9(4x-5)
6. ### Math

Expand and simplify For + 5(a+8)= And for - 7(3d-6)
7. ### Math

How do you expand and simplify (x-2)(x+2)?
8. ### Math

Expand and simplify (p+3)(p-7)
9. ### Urgent math

so I tried to expand this question and I got x^3 *x2, i don't know if it's right but if not can I get a step by step explanation please, Expand (2x + y^2)^5. (Simplify your answer completely.)
10. ### Algebra

need help checking Create a 2-column proof for the following equation. X + X + 10 + 2(2X + 10) = 180 X + X + 10 + 2(2X + 10) = 180 (Given) 2X + 10 + 2(2X + 10) = 180 (Simplify) 2X + 10 + 4X + 20 = 180 (Expand) 6X + 30 = 180 (Simplify) …

More Similar Questions